Case Study: Turnaround Strategy - The Case of Malaysian Marble Sdn. Bhd. (Malaysian Management Journal, 1992)
Malaysian Marble Sdn. Bhd. (MMSB) incorporated in 17 June, 1981 was established to quarry and process marble from the limestone quarries of Pulau Pelangi. When MMSB started their commercial production in the mid of 1983, the positive revenues anticipated was never achieved. Instead the company experienced losses for that year and also for the subsequent years. By 1986, the company wane almost auctioned for a price of $5 million. Hence, Consultant Managers (CM), was brought in to help the ailing company in 1987. Generally, the purpose of the sdudy is to identify the weaknesses of MMSB before turnaround and to evaluate the present stage of the company after CM came into the picture. The researchers adopted presonal interview method in handling the study. From the information gathered, there had been a lot of functional problems like management, marketing, production and finance. Until now, CM had undertook several corrective measures. However, it has still not achieved its target to turnaround MMSB completely.